đặt a-1=x ; b-1=y; c-1=z (x,y,z>0)
\(P=\frac{\left(x+1\right)^2}{x}+\frac{2\left(y+1\right)^2}{y}+\frac{3\left(z+1\right)^2}{z}\)
\(=\frac{x^2+2x+1}{x}+\frac{2y^2+4y+2}{y}+\frac{3z^2+6z+3}{z}\)
\(=x+2+\frac{1}{x}+2y+4+\frac{2}{y}+3z+6+\frac{3}{z}\)
\(=\left(x+\frac{1}{x}\right)+\left(2y+\frac{2}{y}\right)+\left(3z+\frac{3}{z}\right)+12\)
Với x,y,z>0 áp dụng bđt AM-GM ta có: \(x+\frac{1}{x}\ge2\sqrt{x\cdot\frac{1}{x}}=2\)
\(2y+\frac{2}{y}\ge2\sqrt{2y\cdot\frac{2}{y}}=4;3z+\frac{3}{z}\ge2\sqrt{3z\cdot\frac{3}{z}}=6\)
Suy ra \(P\ge2+4+6+12=24\)
Dấu "=" xảy ra \(\Leftrightarrow\left\{{}\begin{matrix}x=\frac{1}{x}\\2y=\frac{2}{y}\\3z=\frac{3}{z}\end{matrix}\right.\Leftrightarrow x=y=z=1\Leftrightarrow a=b=c=2\)